Design and Fabrication of a Microcontroller-Based Automatic LED Grow Light Array System for Leafy Vegetables in Indoor Vertical Hydroponic - Muhammad Achirul Nanda; Muhammad Saukat; Kharistya Amaru; Sophia Dwiratna; Muchamad Ricky Wibo Cahyono (Jurnal Keteknikan Pertanian, 2025)
Indoor vertical hydroponic systems require precise and energy-efficient lighting to support optimal growth of leafy vegetables. This study presents the design and fabrication of a microcontroller-based automatic LED grow light system tailored for indoor hydroponics. A tailored LED grow light is necessary because each crop responds uniquely to light quality and intensity, and a customized spectrum ensures optimal growth while minimizing energy use. The system integrates a red–green–blue LED configuration (70:10:20%) with an ESP32 microcontroller, real-time clock (RTC), BH1750 light sensor, keypad interface, and LCD. The lighting cycle was programmed for 12 hours per day and tested continuously over two days. The system demonstrated accurate scheduling, with LED activation at 06:00 and deactivation at 18:00 and a timing deviation of only 1–2 seconds. During operation, the system maintained a stable photosynthetic photon flux density (PPFD) of 260–275 µmol/m²/s, producing an estimated daily light integral (DLI) of about 12 mol/m²/day, which is suitable for leafy vegetable production. Light distribution analysis using cubic interpolation showed that increasing the lamp height from 20 cm to 30 cm improved spatial uniformity, with the most uniform distribution achieved at 30 cm despite a slight reduction in intensity. The system consumed 2.65 kWh per day, covering four LED arrays and the control module. Overall, the proposed system offers a reliable, programmable, and energy-efficient lighting solution for indoor hydroponic environments, supporting sustainable crop production through precise scheduling and an optimized spectral configuration.